Enhanced Drug Skin Permeation by Azone-Mimicking Ionic Liquids: Effects of Fatty Acids Forming Ionic Liquids - Takeshi Oshizaka; Shunsuke Kodera; Rika Kawakubo; Issei Takeuchi; Kenji Mori; Kenji Sugibayashi (Pharmaceutics)
Background/Objectives: Laurocapram (Azone) attracted attention 40 years ago as a compound with the highest skin-penetration-enhancing effect at that time; however, its development was shelved due to strong skin irritation. We had already prepared and tested an ante-enhancer (IL-Azone), an ionic liquid (IL) with a similar structure to Azone, consisting of ε-caprolactam and myristic acid, as an enhancer candidate that maintains the high skin-penetration-enhancing effect of Azone with low skin irritation. In the present study, fatty acids with different carbon numbers (caprylic acid: C8, capric acid: C10, lauric acid: C12, myristic acid: C14, and oleic acid: C18:1) were selected and used with ε-caprolactam to prepare various IL-Azones in the search for a more effective IL-Azone. Methods: Excised porcine skin was pretreated with each IL-Azone to assess the in vitro skin permeability of antipyrine (ANP) as a model penetrant. In addition, 1,3-butanediol was selected for the skin permeation test to confirm whether the effect of IL-Azone was due to fatty acids and if this effect differed depending on the concentration of IL-Azone applied. Results: The results obtained showed that C12 IL-Azone exerted the highest skin-penetration-enhancing effect, which was higher than Azone. On the other hand, many of the IL-Azones tested had a lower skin-penetration-enhancing effect. Conclusions: These results suggest the potential of C12 IL-Azone as a strong and useful penetration enhancer.